2020
DOI: 10.3171/2020.2.spine191181
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for obtaining solid fusion at L5–S1 in adult spinal deformity: risk factor analysis for nonunion at L5–S1

Abstract: OBJECTIVEMaintaining lumbosacral (LS) arthrodesis and global sagittal balance after long fusion to the sacrum remains an important issue in the surgical treatment for adult spinal deformity (ASD). The importance and usefulness of LS fixation have been documented, but the optimal surgical long fusion to the sacrum remains a matter for debate. Therefore, the authors performed a retrospective study to evaluate fusion on CT scans and the risk factors for LS pseudarthrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Nemoto et al 35 studied CT data from 50 patients who underwent one-level TLIF, using local bone graft materials, and reported that the titanium cage group showed a higher fusion rate than the PEEK cage group. According to a study by Lee et al, 25 based on CT scans, fusion rates after L5-S1 interbody fusion were higher in patients in whom a titanium-made ALIF cage had been used than in those patients with PEEK-made ALIF cages. Third, the disc height after interbody fusion surgery was greater and significantly more increased in the ALIF group than in the TLIF group; the DH at 2 years was 17.9 mm for the ALIF group and 13.2 mm for the TLIF group (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nemoto et al 35 studied CT data from 50 patients who underwent one-level TLIF, using local bone graft materials, and reported that the titanium cage group showed a higher fusion rate than the PEEK cage group. According to a study by Lee et al, 25 based on CT scans, fusion rates after L5-S1 interbody fusion were higher in patients in whom a titanium-made ALIF cage had been used than in those patients with PEEK-made ALIF cages. Third, the disc height after interbody fusion surgery was greater and significantly more increased in the ALIF group than in the TLIF group; the DH at 2 years was 17.9 mm for the ALIF group and 13.2 mm for the TLIF group (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…We excluded these from the analysis because these failures are known not to be related to lumbosacral pseudoarthrosis, but the mobility of the sacroiliac joint, and are considered to be minor failures that do not deteriorate the clinical outcomes. 24,25 Because the follow-up duration was significantly longer in the TLIF group, we had to consider the time to calculate the metal failure rate. Thus, in this study, we performed Kaplan-Meier survivorship analysis with the log-rank test to calculate and compare the metal failure-free probability between the ALIF and TLIF groups.…”
Section: Evaluation Of Fusion On Ctmentioning
confidence: 99%
“…We considered this a limitation of this retrospective study. Several studies have reported that interbody fusion was an important factor in RFs and pseudarthrosis [ 5 , 11 , 19 ], and that the cage material made a difference [ 11 ]. We agree with these opinions and mainly performed interbody fusion at the lumbosacral junction following ASD surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior column support using fusion cages could enhance the fusion rate and prevent implant failure at LSJ ( Jung et al, 2019 ; Lee et al, 2020 ). However, osteoporosis is a risk factor for cage subsidence, with a high prevalence of 32.8% in ASD patients undergoing long spinal fusion ( Gupta et al, 2021 ; Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%